Frontiers of metal-coordinating drug design. (4th May 2021) - Palermo, Giulia; Spinello, Angelo; Saha, Aakash; Magistrato, Alessandra
ABSTRACT: Introduction: The occurrence of metal ions in biomolecules is required to exert vital cellular functions. Metal-containing biomolecules can be modulated by small-molecule inhibitors targeting their metal-moiety. As well, the discovery of cisplatin ushered the rational discovery of metal-containing-drugs. The use of both drug types exploiting metal–ligand interactions is well established to treat distinct pathologies. Therefore, characterizing and leveraging metal-coordinating drugs is a pivotal, yet challenging, part of medicinal chemistry. Area covered: Atomic-level simulations are increasingly employed to overcome the challenges met by traditional drug-discovery approaches and to complement wet-lab experiments in elucidating the mechanisms of drugs' action. Multiscale simulations, allow deciphering the mechanism of metal-binding inhibitors and metallo-containing-drugs, enabling a reliable description of metal-complexes in their biological environment. In this compendium, the authors review selected applications exploiting the metal–ligand interactions by focusing on understanding the mechanism and design of (i) inhibitors targeting iron and zinc-enzymes, and (ii) ruthenium and gold-based anticancer agents targeting the nucleosome and aquaporin protein, respectively. Expert opinion: The showcased applications exemplify the current role and the potential of atomic-level simulations and reveal how their synergic use with experiments can contribute to uncover fundamental mechanistic facets and exploit metal–ligand interactions in medicinal chemistry.